The effects of added salt in the phase II starter pig diet - Kerr, C.A.; Richert, B.T.; Bergstrom, J.R.; Nessmith, W.B.; Goodband, Robert D.; Tokach, Michael D.; Nelssen, Jim L.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A total of 178 pigs (initially 10.5 Ib and 19 d of age) was used to compare the effects of added salt in the Phase II (d 14 to 28 postweaning) diet. Pigs were alloted by sex and inital weight and placed in pens containing either nine or 10 pigs. All pigs were fed the same Phase I diet for the first 14 d postweaning. The Phase I diet contained 20% dried whey, 7.5% spry-dried porcine plasma (SDPP), and 1.75% spray-dried blood meal (SDBM) and was formulated to contain 1.5% lysine and .42% methionine. On day 14, pigs were assigned to one of three diets that contained either 3.5 or 7 lb/ton added salt or no salt. The Phase II diet was cornsoybean meal-based, contained 10% dried whey and 2.5% SDBM, and was formulated to contain 1.25% lysine and .34% methionine. During Phase I (d 0 to 14 postweaning), average dally gain (ADG), average daily feed intake (ADFI), and feed efficiency (F/G) were .52 Ib, .63 Ib, and 1.2, respectively. During Phase II (d 14 to 28 postweaning), ADG and F/G tended to improve with increasing added salt (8 and 9 %, respectively). For the cumulative period (d 0 to 28 postweaning), numerical increases also occurred in both ADG and F/G. These results suggest that up to 7 lb/ton of added salt in a Phase II diet containing 10% dried whey improves ADG and F/G of starter pigs.
Keywords: Swine; Starter; Performance; Salt